(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті розглянуто проблеми управління експериментальною діяльністю в закладах загальної поміжньої освіти. Порушено питання організації та керівництва педагогічними експериментами. Ключові слова: педагогічний експеримент, управління інноваційною діяльністю, інноваційна діяльність, керівництво педагогічним експериментом. In the article the problems of management experimental activity are examined in general schools. The questions of organization and managing pedagogical experiments rise. Key words: pedagogical experiment, management innovative activity, innovative activity, managing a pedagogical experiment.